Rancang Bangun Web-Desa Sebagai Sarana Transparansi Keuangan Dan Kegiatan Di Desa Seloliman Kecamatan Trawas Mojokerto - Achmad Setiawan; M Nur Sulaiman; Burhan Fahzri (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The Regulation of the Minister of Villages, Disadvantaged Regions and Transmigration No. 11 of 2019 as a follow-up to Law number 6 of 2014 stated that there is a priority for village funds to develop a Village Information System (SID) which can be used as a means of promoting village potential, transparency of village finances and information on the dynamics of village community activities. The main problems faced by Seloliman Village, Trawas District, Mojokerto Regency regarding this SID are the absence of skilled personnel in the IT field and the incomplete understanding of village officials regarding the use of the SID. This service aims to help the Seloliman village government build a SID, in this case, a village website that is relatively simple, easy to maintain, intuitive, and most importantly can be handled independently by the village. This service activity is divided into several stages: initial investigation, problem determination, solution search, activity implementation and final evaluation. The results of the dedication show that the designed village website meets the expectations of the Seloliman village community, and is quite informative, intuitive, and easy to update. The Seloliman village administration hopes that the village website can be further developed to become an online village correspondence service facility.